Relação nitrogênio não proteico e proteína verdadeira em suplementos na recria de bezerros Nelore - Fernandes, Rodolfo Maciel [UNESP] (2014)
The objective of this study was to evaluate the effect of elevated protein intake and also different rates of protein degradation, coupled with the use of energy on performance, fermentation parameters, forage intake and supplement in Nellore, recreated in Brachiaria brizantha. Marandu during the dry season transition waters. The treatments were: energy protein supplement with 25% CP (C-25), energy protein supplement with 40% CP, 1/3 of the PB of vegetable and two thirds of urea (40-2/3 NNP) energy protein supplement with 40% CP, 1/3 of the PB urea and 2/3 of vegetable origin (40-1/3NNP), energy protein supplement with 40% CP, 1/2 PB of urea and 1/2 of vegetable origin (40-1/2 NNP). The pasture assessments and weights of animals were taken every 28 days. Each period also estimates individual and collective consumption of supplement and forage plus fermentation parameters were performed. The experimental design was a complete randomized to evaluate the performance blocks, experimental areas and the blocking factor paddock as the experimental unit. Evaluations of ruminal fermentation and the consumption design was a Latin square (4X4). There were no treatment effects on ruminal pH, acetate, propionate and isobutyrate, however, the animals fed supplement with high levels of protein and higher degradation rate (40-2/3NNP), have higher ruminal concentrations of butyrate and isovalerate. There was interaction between treatments and periods of assessment on animal performance. The animals supplemented with higher levels of protein combined with lower rates of protein degradation (40-1/3 NNP) exhibit superior performance when compared to animals consuming lower levels of protein (C- 25) or high levels of protein with high degradation rates (40-2/3 NNP) at the beginning of the transition dry waters . We conclude that elevated levels of protein combined with lower rates of degradation is an alternative ...